Peran Manajemen Pengelola Perpustakaan dalam Meningkatkan Minat Baca Siswa di SMP Plus Maarif NU Parigi Kabupaten Pangandaran - Suryana Suryana; Evi Erfiyana (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
This research is motivated by the development of reading interest and reading ability which is indeed very concerning at this time, how not, this is caused by the methods given to students and students in general are less or even unpleasant, most of the existing methods are only result-oriented not on process. This very low reading habit makes the ability of some students at school to be low. Libraries as educational institutions and information providers will have good performance if they are supported by adequate management, so that all institutional activities will lead to efforts to achieve the goals that have been proclaimed. The focus of his research is the role of library management in an effort to increase students' reading interest. This study uses a qualitative research method using a descriptive approach which is presented in the first and second chapters, each of which discusses the introduction and literature review, while the data exposure and research discussion is in the fourth chapter. The data collection technique used the method of interview, observation and documentation as well as collecting valid documents and data. Planning for school library service standards at SMP Plus Maarif NU Parigi includes; library material planning, human resource planning, facilities and infrastructure planning, service planning and budget planning. Implementation of library management includes; implementation of library material processing, implementation of organizing human resources, implementation of structuring library infrastructure, implementation of library services tailored to the needs and implementation of budget use Evaluation and supervision of libraries is carried out by school principals and vice principals in the field of curriculum.